2020
DOI: 10.1111/ejn.14947
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous EEG and pupillary evidence for post‐error arousal during a speeded performance task

Abstract: Arousal evoked by detecting a performance error may provide a mechanism by which error detection leads to either adaptive or maladaptive changes in attention and performance. By pairing EEG data acquisition with simultaneous measurements of pupil diameter, which is thought to reflect norepinephrinergic arousal, this study tested whether transient changes in EEG oscillations in the alpha frequency range (8–12 Hz) following performance mistakes may reflect error‐evoked arousal. In the inter‐trial interval follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Also, the results showed a strong inverse correlation between pupillary response and fronto-central EEG alpha power during standing with eyes occluded and dual-task eyes occluded conditions. Previous studies demonstrated increased pupillary response and decreased EEG alpha power during cognitive testing suggesting these neurophysiological outcomes re ect increased cognitive workload and attention(Sei Ala, Graversen et al 2020, Compton, Gearinger et al 2021). In the present study, we measured these outcomes during increased postural task di culty in young adults and observed similar results.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the results showed a strong inverse correlation between pupillary response and fronto-central EEG alpha power during standing with eyes occluded and dual-task eyes occluded conditions. Previous studies demonstrated increased pupillary response and decreased EEG alpha power during cognitive testing suggesting these neurophysiological outcomes re ect increased cognitive workload and attention(Sei Ala, Graversen et al 2020, Compton, Gearinger et al 2021). In the present study, we measured these outcomes during increased postural task di culty in young adults and observed similar results.…”
Section: Discussionmentioning
confidence: 94%
“…The present study addresses mechanisms of cognitive control with a specific focus on understanding how detection of performance errors may lead to neurocognitive adjustments in processing. As in prior work, we consider two broad models of error-related cognitive control, the maladaptive arousal model and the adaptive control model (Compton et al, 2021). These models make different predictions about how detecting a performance error affects subsequent cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha suppression may be caused by the same noradrenergic increase that leads to pupil dilation; for example, vagus nerve stimulation, which activates the locus coeruleus norepinephrinergic system, leads to simultaneous pupil dilation and alpha suppression (Sharon et al, 2021). Pupillary and EEG markers of arousal co-vary during cognitive performance, such that trials with higher levels of pupil dilation following a response tend to have higher levels of alpha suppression in that same interval (Compton et al, 2021). Together these findings support the expectation that errors are followed by arousal measured by both peripheral (pupillary) and central (EEG) indices.…”
Section: Introductionmentioning
confidence: 99%
“…Because slowing down after an error is sometimes associated with an increase in accuracy, PES is traditionally attributed to adaptive adjustments of decision policies, favoring a more cautious response style to improve performance in the subsequent trial (Rabbitt and Vyas 1970, Smith and Brewer 1995, Cavanagh et al 2014, Siegert et al 2014, Purcell and Kiani 2016, Steinhauser and Andersen 2019, Beatty et al 2020). However, several recent studies have revealed that PES can also occur in a somewhat ‘maladaptive’ way as slowing does not necessarily lead to improvement in accuracy; in fact, PES can even come with a decrease in decision accuracy (Ceccarini et al 2019, Eben et al 2020b, Kirschner et al 2020, Schroder et al 2020, Smith et al 2020, Compton et al 2021). These findings indicate that the functional significance of PES may vary according to the context in which it is observed.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, studies reporting a maladaptive PES rather use reaction time tasks that are quite simple such that the overall level of choice accuracy is usually much higher (i.e. more between 80 – 100% of correct choices) (Notebaert et al 2009, Nunez Castellar et al 2010, Houtman et al 2012, Eben et al 2020b, Kirschner et al 2020, Li et al 2020, Compton et al 2021). In such settings, errors represent infrequent and unexpected events that may catch attention, resulting in a maladaptive PES that deteriorates (rather than enhances) choice accuracy in the consecutive trial (Sokolov 1963, Nunez Castellar et al 2010, Houtman et al 2012).…”
Section: Introductionmentioning
confidence: 99%